Eksplorasi Tumbuhan Obat Indonesia untuk Kebugaran: Analisis Data Riset Tumbuhan Obat dan Jamu Tahun 2012, 2015, dan 2017 - Kristiana, Lusi; Paramita, Astridya; Maryani, Herti; Andarwati, Pramita (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2022)
Compounding plants into health ingredients is a promotive-preventive-based health culture, which was identified in the Research on Medicinal Plants and Herbs (Ristoja). The regeneration of traditional healers who mastered herbal formulation is not going well, documentation must be carried out for better knowledge transfer process. This study documented the traditional use of plants to preserve health and fatigue, using data from Ristoja 2012, 2015 and 2017, obtained from the National Institute of Health Research and Development (Indonesian Ministry of Health), data were analyzed descriptively. The data inventory includes grouping of species-family, plant parts, method, frequency, and duration of use, cultivation/non-cultivation, origin, and method of obtaining plants. The results show that the ingredients to preserve health and relieve fatigue have a large diversification, namely 33 families and 60 species. The most widely used are from families Zingiberaceae and Myrtaceae; species Z. officinale, C. domestica, C. xanthorrhiza, P. guajava, S. aromaticum, and S. Polyantum; parts of plant leaves (71,7%) and roots (38,3%;, originally from yards, forests, and fields/gardens; mostly consumed once/day (76,7%). Plants that have been used as ingredients to preserve health and relieve fatigue have several mechanism of action, such as antioxidant, anti-inflammatory, analgesic, glycemic control, blood pressure control, and others.